2008
DOI: 10.1158/0008-5472.can-08-0222
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimethamine Induces Apoptosis of Melanoma Cells via a Caspase and Cathepsin Double-Edged Mechanism

Abstract: The unresponsiveness of metastatic melanoma to conventional chemotherapeutic and biological agents is largely due to the development of resistance to apoptosis. Pyrimethamine belongs to the group of antifolate drugs, and in addition to antiprotozoan effects, it exerts a strong proapoptotic activity, which we recently characterized in human T lymphocytes. However, no data regarding pyrimethamine anticancer activity are available thus far. To this end, we examined the in vitro effects of pyrimethamine on apoptos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
55
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 42 publications
(53 reference statements)
10
55
1
4
Order By: Relevance
“…PYR has been shown to reduce melanoma growth in a severe combined immune-deficient mouse model (40). Consistent with previous reports (39,40), we observed that PYR at a concentration of 0.5 μmol/L increased the number of cells in S phase (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…PYR has been shown to reduce melanoma growth in a severe combined immune-deficient mouse model (40). Consistent with previous reports (39,40), we observed that PYR at a concentration of 0.5 μmol/L increased the number of cells in S phase (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that PYR can induce apoptosis and S phase accumulation in various cell lines (37)(38)(39)(40). PYR has been shown to reduce melanoma growth in a severe combined immune-deficient mouse model (40).…”
Section: Discussionmentioning
confidence: 99%
“…As suggested, ROS are critical regulators of caspase 8-mediated apoptosis. Accordingly, in a study with pyrimethamine in metastatic melanoma, it was found that the drug, which generates ROS, induced upstream caspase activation (caspase 8), bypassing CD95/Fas engagement, similar to what had been previously observed by the same authors in activated lymphocytes from a patient with a lymphoproliferative syndrome (45).…”
Section: Discussionsupporting
confidence: 77%
“…[11][12][13]23 However, inhibition of cathepsin L did not have any effect on TRAILinduced apoptosis (Supplementary Figure 2), whereas inhibition of cathepsin B partially blocked apoptosis induced by TRAIL in only two (ME4405 and Mel-AT) of eight melanoma cell lines (Figure 2b). It should be noted that the two lines were most sensitive to TRAIL (Supplementary Figure 1A), even though there was no overall correlation between the levels of cathepsin B expression and sensitivity of melanoma cells to TRAIL-induced apoptosis (data not shown).…”
Section: Discussionmentioning
confidence: 96%
“…11,12 Moreover, it has been reported to have a role in induction of apoptosis of melanoma cells by the antifolate agent pyrimethamine. 13 The cytosol contains endogenous cysteine cathepsin inhibitors, cystatins, which function as threshold inhibitors to protect cells from detrimental consequences caused by lysosomal release of the cathepsins. 10,14 Among them, cystatin B appears to be of particular interest, in that cystatin B-deficient mice exhibit increased apoptosis of cerebellar granule cells that is associated with the increased expression of apoptosis genes.…”
mentioning
confidence: 99%